Outcomes following endorectal pull-through for Hirschsprung disease: a retrospective study - Amr Abdelhamid AbouZeid; Amr AbdelRahman AbdelMalek (SpringerOpen, 2024)
Abstract Purpose To share our experience in the surgical management of patients with Hirschsprung disease (HD) using the trans-anal endorectal pull-through "Soave" technique. Methods The study included cases diagnosed as HD who were operated during the period 2008 through 2018. Cases of total colonic aganglionosis were excluded to be discussed in a separate report. Results The study included 67 consecutive cases of HD. All included cases underwent trans-anal endorectal pull-through which was purely trans-anal in 31 (46%), while abdominal-assisted trans-anal endorectal pull-through was applied in the remaining (54%). Early postoperative complications included 2 cases of partial dehiscence at the colo-anal anastomosis; 1 of them deteriorated after re-exploration and unfortunately died. Twenty-six cases were available to assess functional outcomes after corrective surgery. Their age at follow-up ranged between 44 months and 17 years (mean = 78.8 months; median = 72 months). All cases achieved voluntary defecation. However, fecal soiling was a common finding after surgery for HD (69%). Constipation was another common postoperative finding (73%). Lastly, a history of attacks of postoperative enterocolitis was prevalent in 19 cases (73%), which ranged between 1 and 7 attacks usually in the first 2 years after the operation. Conclusion The trans-anal endorectal pull-through provides an effective surgical treatment for Hirschsprung disease. The high prevalence of fecal soiling after surgery highlights the importance of long-term follow-up to provide the required support for these patients during adolescence and transition into adulthood.